Protein Turnover in Malnourished Elderly Subjects: The Effects of Refeeding - BEAUMONT, D.; LEHMANN, A. B.; JAMES, O. F. W. (Age and ageing, 1989)
A primed constant-rate infusion of L-(l-14C)-leucine was used to assess protein flux, synthesis, and breakdown in a group of malnourished elderly subects (n = 9) and a group of age-matched healthy elderly control subjects (n = 9). No significant differences between the two groups were observed in measures of protein metabolism. Four out of six malnourished subjects, restudied after a period of dietary replenishment, showed non-significant increases in protein synthesis and breakdown. Plasma insulin concentrations were significantly suppressed (p < 0.05) and plasma growth hormone and cortisol concentrations significantly elevated (p < 0.05) in the malnourished subjects before and after refeeding compared with the healthy elderly controls.